HUBUNGAN PENGETAHUAN MASYARAKAT TERHADAP KESIAPSIAGAAN MENGHADAPI COVID-19 DI MASYARAKAT DESA TANJAKAN RT.008/RW.003 RAJEG KABUPATEN TANGERANG TAHUN 2021 - Muhamad Firdaus; Garry Vebrian; Ayu Pratiwi (Nusantara Hasana Journal, 2021)
Based on data from the Ministry of Health of the Republic of Indonesia in 2020, COVID-19 cases in the Tangerang Regency area were quite high, with 461 cases being treated, 6,778 recovered and 170 cases dying. Meanwhile, Rajeg District is one of the 10 biggest contributors to the number of Covid-19 cases with 247 cases, 10 cases are still being treated, 2 cases are in isolation, 231 cases have been declared cured and 2 cases have died. Objective: to determine the relationship between public knowledge and preparedness to face Covid-19 in the community of Tanjakan Village RT.008/RW.003 Rajeg, Tangerang Regency in 2021. Research design: using an analytical survey method with a cross sectional approach. Samples were taken using the Slovin formula with a total sample of 134 respondents. Sampling using accidental sampling technique. This study uses univariate and bivariate analysis with Chi Square test. Results: based on univariate analysis, it was obtained from 134 respondents the majority with less preparedness for Covid-19 was 56.7% and for the majority knowledge with poor health knowledge was 50.7%. For bivariate analysis with the chi square test, there was a relationship between public health knowledge and preparedness to face Covid-19, as evidenced by the statistical test results P Value 0.000 with an OR value of 4.920. The conclusion obtained is that there is a relationship between public health knowledge and preparedness to face Covid-19.